An in vitro evaluation of aligner force decay in artificial saliva - Shou-Min Chen; Chun-Te Ho; Tsui-Hsein Huang; Chia-Tze Kao (Elsevier, 2023)
Background/purpose: The present study aimed to compare the force decay of invisible aligners for maxillary anterior teeth with 0.1 mm (D1), 0.2 mm (D2), and 0.3 mm (D3) labial movement within a simulated oral environment over 7 days. Materials and methods: The prepared invisible aligners were immersed in saliva (S) and subjected to applied force (F) for 7 days. The aligners were set and placed on the maxillary right central incisor with 0.1 mm (D1), 0.2 mm (D2), and 0.3 mm (D3) labial movement. Thin-film pressure sensors were used to measure the aligner force changes. The data were collected and analyzed by statistical methods. Results: Significant differences were observed in the initial and first-day force between the D2 and D3 groups under simulated oral environment force (SF) (P < 0.05). There was a significant difference in force decay between Day 1 and Day 7 for all groups (P < 0.05). The SFD1 group showed a significant decrease in force on Day 5 (P < 0.05), while the SFD2 and SFD3 groups showed significant force decay on Day 4 (P < 0.05). The force decay ratio on Day 7 was higher in the SFD3 group than in the SFD1 and SFD2 groups, but no significant difference was observed. Conclusion: Larger labial movement of the aligners resulted in higher force decay under artificial saliva environments, and the force decay of invisible aligners was increased by immersion time in artificial saliva.